2008
DOI: 10.1021/op7001112
|View full text |Cite
|
Sign up to set email alerts
|

Process Research and Development and Scale-up of a 4,4-Difluoro-3,3-dimethylproline Derivative

Abstract: The multikilogram production of the proline derivative 1, a key intermediate of a HIV protease inhibitor, required the design of a synthetic route able to be safely, effectively, and easily scaled up. Synthesis of the proline skeleton began with construction of racemic glycine derivative 4, via an ester enolate Claisen rearrangement of Boc-glycine 3-methyl-but-2-enyl ester (3) in the absence of a Lewis acid. After a classical resolution of 4 with (S)phenylglycinol, (S)-4 was transformed into bromo-lactone 6b w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…(38) For example, previous hazard safety studies reported by Rossi et al on Deoxo-Fluor showed that the onset of decomposition is around 70 °C using a Calvet calorimeter (C80), a value much lower than that detected by DSC (120 °C). (39) Likewise, DAST reportedly undergoes a very energetic decomposition between 50 and 60 °C. (40) It is noteworthy that these figures are somewhat lower than those previously obtained by ARC which showed onsets of decomposition at 85 °C for DAST and 100 °C Deoxo-Fluor.…”
Section: Resultsmentioning
confidence: 99%
“…(38) For example, previous hazard safety studies reported by Rossi et al on Deoxo-Fluor showed that the onset of decomposition is around 70 °C using a Calvet calorimeter (C80), a value much lower than that detected by DSC (120 °C). (39) Likewise, DAST reportedly undergoes a very energetic decomposition between 50 and 60 °C. (40) It is noteworthy that these figures are somewhat lower than those previously obtained by ARC which showed onsets of decomposition at 85 °C for DAST and 100 °C Deoxo-Fluor.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the macrocyclic bis-thiourea 5 promoted the glycosylation with increased yield and selectivity relative to 4 , and a further improvement in catalyst performance resulted from replacement of the chiral arylpyrrolidine moiety with indoline as in 6 (88% yield, 8:92 α:β). The C 2 -symmetric design of 6 offers additional practical advantages as it greatly simplifies catalyst synthesis: starting from known amino acid, 6 was synthesized in 7 steps and 41% yield, with homodimerization as the ultimate step (32). …”
Section: Main Textmentioning
confidence: 99%
“…In view of the importance of fluoro-compounds and chiral Nheterocycles, we envisioned that enantioselective 1,3-dipolar cycloaddition of azomethine ylides with gem-1,1-difluorostyrenes and 1,1,2-trifluorostyrenes would lead to a broad scope of biologically active fluoropyrrolidines. [62][63][64][65][66][67][68] To achieve this transformation, two challenges need to be considered (Scheme 1d). It is well known that the dipolarophiles of the 1,3-dipolar cycloaddition of azomethine yilde are generally limited to highly activated olefins bearing strong electron withdrawing substituents, [29][30][31][32][33][34] and only a few cases are associated with less reactive olefins, however, the utilization of inactive alkenes as dipolarophiles remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%